The Effect of Competency And Locus of Control On Accounting Student's Jobreadiness - Ratal, Muhammad Ratal; Hasanah, Nuramalia; Zakaria, Adam (LPPM Universitas Negeri Jakarta, 2022)
This study examined the impact of accounting students' ethical competence, knowledge competence, ability competence, relationship competence, analytical competence, and locus of control on their job-readiness. This study utilizes primary data in the form of a questionnaire distributed to accounting students in the UNJ Faculty of Economics. This study's population consisted of undergraduate accounting students who were eligible to enrollin thesis courses and were still participating in odd semester lectures for the academic year 2021/22. This study's sample selection employed a technique of purposive sampling and yielded a study sample of 100 respondents. This research employs quantitative methods. Descriptive statistical analysis and multiple linear regression analysis are used for analysis. This study's findings indicate that ethical competence, knowledge competence, ability competence, relationship competence, and locus of control positively influence accounting students' job-readiness. Meanwhile, analytical ability has no bearing on accounting students' work readiness.